Breaking Barriers? : Social inequality in pathways to higher education between general and vocational schools in Germany - Winkler, Oliver [Verfasser]; Busse, Robin [Verfasser]; Stefanie Findeisen [Verfasser] (My University, 2025)
“Pathways to higher education through vocational upper secondary schools (VUSSs) are intended to increase permeability. However, in both VUSSs and general upper secondary schools (GUSSs), participation is socially selective. This article examined differences between GUSS and VUSS students in (a) the attainment of a higher education entrance qualification (HEEQ) and (b) the subsequent transition to higher education. Taking entry selectivity into account, we analysed the extent to which inequalities between GUSS and VUSS in both outcomes could be explained by differences in school achievement and educational considerations—namely, cost–benefit perceptions, expected success, and status maintenance motives. Using data from the German National Educational Panel Study (NEPS; Starting Cohort 4), we selected a sample of individuals who entered upper secondary education in either VUSS or GUSS (N = 5032). Two binary dependent variables were used to indicate (a) the successful attainment of an HEEQ and (b) the subsequent transition to higher education (as opposed to vocational education and training). The results from logit models indicated that VUSS students were significantly less likely to obtain an HEEQ and progress to higher education. This association was smaller but still persistent when controlling for entry selection, school achievement, and educational considerations (AMEHEEQ = −0.047, AMEtransition = −0.150). However, when intake selection was considered in the logit models, school achievement and educational considerations during upper secondary education were insignificant in explaining why VUSS students were less likely than GUSS students to obtain an HEEQ and enter higher education.” (authors‘ abstract; BIBB-Doku)
Keywords: P 2.1.5 Fachhochschul- und Hochschulreife; S 1.1 Allgemeinbildende Schule; S 3.1.3.1 Berufliches Gymnasium; 370; Hochschulzugang; Studienberechtigung; Gymnasium; Berufliches Gymnasium; Ungleichheit; Durchlässigkeit im Bildungssystem